2002
DOI: 10.1021/jf011175a
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Synergistic Effect of Linolenic Acid and Monoglyceride against Bacillus cereus and Staphylococcus aureus

Abstract: The antimicrobial effect of linolenic acid with or without monoglyceride (glycerol laurate or glycerol myristate) against six food-borne microorganisms was determined in broth medium. Minimum inhibitory concentration of linolenic acid on Bacillus cereus and Staphylococcus aureus was 20 and 50 ppm, respectively. The growth of B. cereus treated with linolenic acid at 10 ppm with 10 ppm monoglyceride was more inhibitory than that of linolenic acid alone, and the viable cell population was reduced 2-4 log cycles c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 15 publications
4
73
1
4
Order By: Relevance
“…The inhibitory concentrations of MAG-C12:0 of B. cereus or B. anthracis are within the range of 25-70 mg·l -1 (Lee et al 2002;Preuss et al 2005). Our results also correspond to these values.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The inhibitory concentrations of MAG-C12:0 of B. cereus or B. anthracis are within the range of 25-70 mg·l -1 (Lee et al 2002;Preuss et al 2005). Our results also correspond to these values.…”
Section: Discussionsupporting
confidence: 88%
“…aureus CCM 3953, the inhibition of which was caused by this MAG at a concentration of 250 mg·l -1 . This minimum inhibitory concentration is higher than the one detected in other strains of staphylococci (Lee et al 2002;Růžička et al 2003;Preuss et al 2005).…”
Section: Discussioncontrasting
confidence: 55%
“…The ethanolic extract of D. salina (Table 2) showed antibacterial activity against the Gram-negative bacteria, E. coli and P. aeruginosa and no activity against the Gram-positive bacterium S. aureus. If this activity was mainly attributed to the linolenic acid which was found to be abundant in the tested extract, then our observations regarding S. aureus are in contrast to those by Lee et al (2002). The extract from N. gaditana was shown to contain important amounts of palmitoleic acid (cis-9-hexadecenoic acid) (28%), palmitic acid (24.1%), oleic acid (15.3%) and eicosapentaenoic acid (14%).…”
Section: Microalgaementioning
confidence: 62%
“…The analysis of the ethanolic extract from D. salina showed that this microalga contains the highest amount of ethanol extractable PUFA, being 76.9 % of which linolenic acid (all-cis-9,12,15-octadecatrienoic acid) constitutes a high part (45.3%) (Maadane et al, 2015). According to Lee et al (2002), the antimicrobial activity of linolenic acid was high against Gram-positive bacteria, but low against Gram-negative bacteria. The ethanolic extract of D. salina (Table 2) showed antibacterial activity against the Gram-negative bacteria, E. coli and P. aeruginosa and no activity against the Gram-positive bacterium S. aureus.…”
Section: Microalgaementioning
confidence: 99%
“…To determine the efficacy of G. biloba leaf essential oil on the membrane integrity, concentration of extracellular adenosine 5'-triphophate (ATP) was measured according to the method described previously (Lee et al, 2002). The working culture of B. cereus ATCC 13061 and E. coli ATCC 43889 containing approximately 10 7 CFU/mL were centrifuged for 10 min at 1,000 g and the supernatants were removed.…”
Section: Measurement Of Extracellular Adenosine 5'-triphophate Concenmentioning
confidence: 99%